Pengaruh Tingkat Kesehatan Bank Umum Syariah di Indonesia Terhadap Pertumbuhan Laba Pada Periode 2020-2024 - Nabila, Rasyifa Suci; Mansur, Fitriani; Safelia, Nela (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This study examines the effects of NPF, FDR, ROA, BOPO, CAR, and GCG on the profit growth of Islamic Commercial Banks in Indonesia during 2020–2024 using panel data regression. The results indicate that FDR has a positive and significant effect, while BOPO has a negative and significant effect on profit growth. Other variables show no significant effect. Simultaneously, all variables significantly influence profit growth, with the model explaining 33.42% of its variation. The findings emphasize the importance of liquidity management and operational efficiency in enhancing profit growth. These results provide empirical insights for bank management and regulators in formulating strategies to improve financial performance.